Who captures value in global supply chains? Case Nokia N95 smartphone - Jyrki Ali-Yrkkö; Petri Rouvinen; Timo Seppälä (The Research Institute of the Finnish Economy (ETLA), 2011)
Available statistics tell us little about the economic consequences of increasing global dispersion of production processes. In order to shed light on the issue, we perform grass roots detective work to uncover the geography of value added in the case of a Nokia N95 smartphone circa 2007. The phone was assembled in Finland and China. In the case when the device was assembled and sold in Europe, the value-added share of Europe (EU-27) rose to 68%. Even in the case when it was assembled in China and sold in the United States, Europe captured as much as 51% of the value added, despite of the fact that it had little role in supplying the physical components. Our analysis illustrates that international trade statistics can be misleading; the capture of value added is largely detached from the physical goods flows. It is rather services and other intangible aspects of the supply chain that dominate. While final assembly - commanding 2% of the value added in our case - has increasingly moved offshore, the developed countries continue to capture most of the value added gener-ated by global supply chains.
Keywords: F14; F23; L22; L23; 330; global supply chains; international trade; value capture